PERCEPTION UNDERSTANDING AND ATTITUDE OF HOUSEWIVES IN ECOSYSTEM MANAGEMENT - Utami, Linda (Jurnal Manajemen, 2024)
The method used in this study is the experimental and descriptive method, namely description, explanation, and analysis. The population in this study were housewives in the Musi Hilir River Basin Area, Palembang City, which consists of the base zone, namely Gandus Village, the middle zone, namely 7 Ulu Village and 16 Ilir Village, while the end zone is Sungai Lais Village. The samples taken in this study were for the base zone, middle zone and end zone. Determination of the sample in this study used the purposive sampling method, meaning that there is a specific purpose to describe a particular social symptom or social problem. from the study obtained that the perception of housewives based on education experienced differences, the understanding of housewives based on education did not differ and the attitude of housewives based on education had a good attitude towards managing aquatic ecosystems.